2019
DOI: 10.1002/fam.2792
|View full text |Cite
|
Sign up to set email alerts
|

Electrical component ignition in a closed enclosure adjacent to a controlled fire

Abstract: Summary Electrical cabinet fires are one of the main fire hazards in nuclear power plants (NPPs). The electrical cabinets are often arranged in rows of adjacent cabinets (ACs) in NPPs. So the ability of a cabinet fire to spread to ACs is a major concern for fire safety. This work aims to investigate the impact on the fire spread of the air gap between two electrical cabinets, the electrical component type contained in the AC, and its ventilation mode. For that purpose, a test device composed of two adjacent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 9 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…The expanded relative uncertainty for the two HFS was estimated in this study to be ± 15 %. This is consistent with the evaluations given in other fire test conditions [9] and [12] for the same type of sensor. Three cameras were used for these tests.…”
Section: Instrumentationsupporting
confidence: 92%
See 4 more Smart Citations
“…The expanded relative uncertainty for the two HFS was estimated in this study to be ± 15 %. This is consistent with the evaluations given in other fire test conditions [9] and [12] for the same type of sensor. Three cameras were used for these tests.…”
Section: Instrumentationsupporting
confidence: 92%
“…The back wall contribution is indeed negligible. Previous research [9] showed that maximum wall temperatures of the BE, for the same fire power of 300 kW, did not exceed 850 K at 300 s. Thus, considering this temperature in Eq. ( 1), as well as a maximum view factor of 0.145 (SD of 0.4 m) for dA to the back wall FdA-BW (see appendix A) and a steel wall emissivity of 0.8, this gives a maximum contribution of 3 kW/m2 to q0, before taking into account the flame absorption.…”
Section: Tests Without a Front Panelmentioning
confidence: 85%
See 3 more Smart Citations